2023
DOI: 10.1007/s11356-023-29704-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable pathways for attaining net-zero emissions in European emerging countries — the nexus between renewable energy sources and ecological footprint

Sunil Tiwari,
Arshian Sharif,
Florian Nuta
et al.

Abstract: This study aims to investigate the relationship between renewable energy and ecological footprint during the period of 1994-2018 from selected developing countries in Europe (Czechia, Croatia, Poland, Romania, Romania, and Turkey). In this context, the ecological footprint (EF), which has recently been the most widely used environmental indicator in the literature and is known as the most comprehensive because it includes many environmental factors, has been determined as the dependent variable. As independe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Following this approach [90], other concepts should be considered that affect greenhouse emission, like the ecological footprint, which is considered another important concept in the literature, as well as the environment variables, like renewables energy consumption, energy-related tax revenue, and energy productivity, that show a good relationship of cause-effect. Therefore, investments, expenses, or taxes related to the environment allow a reduction in climate change and an improvement of the health of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Following this approach [90], other concepts should be considered that affect greenhouse emission, like the ecological footprint, which is considered another important concept in the literature, as well as the environment variables, like renewables energy consumption, energy-related tax revenue, and energy productivity, that show a good relationship of cause-effect. Therefore, investments, expenses, or taxes related to the environment allow a reduction in climate change and an improvement of the health of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research articles listed in Table 3, including works by Philip et al [29], Sahoo and Sethi [36], Nathaniel et al [45], Usman et al [46], Wang et al [47], Rej et al [48], Abid et al [49], Raza et al [50], Nan et al [51], Wang et al [52], and Abban et al [53], have demonstrated a negative impact of renewable energy use on environmental impairment. However, studies by Raghutla et al [54] and Karada g Albayrak et al [55] identified a positive impact of renewable energy utilization on environmental impairment, while Tiwari et al [56] reported an insignificant relationship between ecological footprint and renewable energy use. Nathaniel et al [45] analyzed the connection between the ecological footprint, renewable energy use, and urbanization in MENA countries from 1990 to 2016 using causality and cointegration tests.…”
Section: Empirical Literature On the Environmental Effects Of Renewab...mentioning
confidence: 98%
“…Tiwari et al [56] discovered an insignificant relationship between ecological footprint and renewable energy in six developing European countries based on causality and cointegration analyses. Finally, Nathaniel and Khan [57] examined the impact of urbanization, economic growth, and non-renewable and renewable energy use on the ecological footprint in ASEAN countries from 1990 to 2016 using causality and cointegration tests.…”
Section: Empirical Literature On the Environmental Effects Of Renewab...mentioning
confidence: 99%
“…In works such as that of Bouwma et al [20], Postul & Radecka-Moroz [21] and Bräuer et al [22] the authors point out that a properly structured tax system can stimulate certain pro-environmental behavior through various preferences, and, on the other hand, discourage activities that damage the environment. Also, Tawari et al [23], in the results of their conducted research, clearly indicate the need to implement appropriate economic policy (including tax) to reduce the so-called ecological footprint and dissemination of green technologies. Similarly, Abban et al [24], who focus more on the issue of reducing carbon dioxide emissions, note the need for active actions in this direction by various regulatory agencies.…”
Section: Literature Reviewmentioning
confidence: 99%